Agricultural Irrigation - Montazar, Aliasghar (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Agriculture is certainly the most important food supplier while it globally accounts for more than 70% of water used and contributes significantly to water pollution. Irrigated agriculture is facing rising competition worldwide for access to reliable, low cost, and high-quality water resources. However, irrigation as the major tool and determinant of affecting agricultural productivity and environmental resources plays a critical role in food security and environment sustainability. Innovative irrigation technologies and practices may enhance agricultural water efficiency and production, in the meantime decrease the water demand and quality issues. I am very pleased to invite you to submit manuscripts in agricultural irrigation which assess current challenges and offer improvement approaches and opportunities for future irrigation.